A Crusader, Ottoman, and Early Modern Aegean Archaeology: Built Environment and Domestic Material Culture in the Medieval and Post-Medieval Cyclades, Greece (13th-20th Century AD), by Athanasios K. Vionis. (9th February 2017) - Manginis, George
Abstract : A Crusader, Ottoman, and Early Modern Aegean Archaeology: Built Environment and Domestic Material Culture in the Medieval and Post-Medieval Cyclades, Greece (13th-20th Century AD), by Athanasios K. Vionis. Archaeological Studies Leiden University 22. Leiden University Press, 2012. 423pp., Pb. €69.50. ISBN-13: 9789087281779.